The Australian Science Teacher: A Typology of Teacher-Student Interpersonal Behaviour in Australian Science Classes - Rickards, Anthony; Den Brok, P.; Fisher, Darrell (Kluwer Academic Publishers, 2005)
This study reports the first development in Australia of science teacher typologies of teacher–student interpersonal behaviour. Students' perceptions of teacher–student interpersonal behaviour were measured using the Questionnaire on Teacher Interaction (QTI). Earlier work with the QTI in The Netherlands has revealed eight different interpersonal styles, which were later confirmed with an American sample of secondary school teachers. The present study investigated the extent to which typologies found in earlier studies also apply to a sample of Australian secondary school science teachers. Data were first checked to examine whether the eight profiles found in The Netherlands and the USA were also present in the Australian data. A cluster analysis using various clustering methods and procedures was used to determine Australian typologies and compare these with earlier Dutch findings. Results of the cluster analyses were verified by analyses of variance, by plotting QTI scale scores graphically, and by presenting a set of sector graphics to two independent researchers and having them sort these into different profiles as found in the statistical analyses. The resultant typologies and implications for professional development and research are presented.